Functional microfluidics: theory, microfabrication, and applications - Mingzhu Xie; Ziheng Zhan; Yinfeng Li; Junkai Zhao; Ce Zhang; Zhaolong Wang; Zuankai Wang (International Journal of Extreme Manufacturing, 2024)
Microfluidic devices are composed of microchannels with a diameter ranging from ten to a few hundred micrometers. Thus, quite a small (10 ^−9 –10 ^−18 l) amount of liquid can be manipulated by such a precise system. In the past three decades, significant progress in materials science, microfabrication, and various applications has boosted the development of promising functional microfluidic devices. In this review, the recent progress on novel microfluidic devices with various functions and applications is presented. First, the theory and numerical methods for studying the performance of microfluidic devices are briefly introduced. Then, materials and fabrication methods of functional microfluidic devices are summarized. Next, the recent significant advances in applications of microfluidic devices are highlighted, including heat sinks, clean water production, chemical reactions, sensors, biomedicine, capillaric circuits, wearable electronic devices, and microrobotics. Finally, perspectives on the challenges and future developments of functional microfluidic devices are presented. This review aims to inspire researchers from various fields—engineering, materials, chemistry, mathematics, physics, and more—to collaborate and drive forward the development and applications of functional microfluidic devices, specifically for achieving carbon neutrality.